Efficacy and Safety of Paliperidone Palmitate Treatment in Patients With Schizophrenia A Real-World Multicenter, Retrospective, Mirror-Image Study - Devrimci-Ozguven, Halise; Atmaca, Murad; Baran, Zeynep; Cengisiz, Cengiz; Cinar, Cem; Erol, Atila; Yildiz, Mesut (Lippincott Williams & Wilkins, 2019)
Purpose The aim of the study was to assess efficacy and safety of paliperidone palmitate (PP) in schizophrenic patients using real-life data. Methods This national, multicenter, retrospective, and mirror-image study was performed reviewing the medical records of patients in 18 centers. Adult schizophrenic patients receiving PP treatment (n = 205) were enrolled. Patients' data covering the last 12 months before the initial PP injection and the period until the end of study with at least 12 months after the initial PP injection were evaluated. Patients' characteristics, scale scores, and adverse events were recorded. Results Nonadherence to prior medication was the most frequent reason for switching to PP treatment. Comparing with the period before PP treatment, the rate of patients visiting the hospital for relapse (79.5% vs 28.9%, P < 0.001) and the median number of hospitalizations (2 vs 0, P < 0.001) were lower during PP treatment. During PP treatment, the Positive and Negative Syndrome Scale score decreased by 20% or more (response to treatment) in 75.7% of the patients. The frequency of adverse events did not differ between the period before and during PP treatment. Improvement in functionality was higher in those with disease duration of 5 years or less. Conclusions Paliperidone palmitate is effective and safe in treatment of schizophrenic patients and in switching to PP treatment in patients with schizophrenia, which reduced the percentage of patients admitted to the hospital for relapse and the median number hospitalization, and has positive effects on functionality.
Keywords: schizophrenia; long-acting injectable antipsychotic; paliperidone palmitate